Quantum spin liquid in the semiclassical regime - Ioannis Rousochatzakis; Yuriy Sizyuk; Natalia B. Perkins (Nature Communications, 2018)
Strongly correlated quantum spin liquid phases form when quantum fluctuations prevent magnetic ordering, which normally requires low spin systems that cannot be analyzed semiclassically. Here, the authors show that a large-spin Kitaev model supports a spin liquid phase in the semiclassical limit.